Para sport athletic identity from competition to retirement: A brief review and future research directions - Guerrero, M.; Martin, J. (Physical Medicine & Rehabilitation Clinics of North America, 2018)
The primary purpose of this article is to review the literature on para sport athletic identity and provide avenues for future research direction. First, the authors briefly describe the existing quantitative and qualitative research on para sport athletic identity and, thereby, illustrate the complexities para sport athletes experience regarding the way they describe their participation in competitive sport. Next, the authors describe how para sport athletes with acquired permanent disabilities and congenital disabilities face similar, yet unique, identity-related challenges. Finally, the authors argue that future researchers should consider examining para sport athletes` identity through narrative identity.